Pelatihan Media Interaktif Untuk Pembelajaran Pengembangan Kemampuan Sosial Anak Usia Dini - Ahmad Fachrurrazi; Titah Kinasih (Universitas PGRI Adi Buana Surabaya, 2022)
The tendency of children's learning patterns that prefer to play affects children's learning motivation, so that theoretical learning alone is not optimal for early childhood learning. Interactive media that can be developed for children's socio-emotional learning such as interactive games, IT-based games developed to get to know the environment, animals, plants, and so on. This community service aims to provide knowledge and skills in using technology by creating interactive media. The problem is the ability of teachers to use simple multimedia applications is still lacking, so the media developed for learning activities is conventional media manually. Teachers need training for interactive media creation. The program offered is training in making simple interactive media based on a power point application. Generally, the results obtained from this service were that participants were able to apply the principles of media for learning that were suitable for early childhood, such as choosing objects that matched the theme, illustrating objects according to their character, such as animals with their characteristics and sounds, their movements, and so on. Participants are also able to create navigation and hyperlinks according to the placement and location of the desired source.